Effects of castration on carcass composition, meat quality, and sensory properties of beef produced in a tropical climate - Rodriguez, Julio (Kansas State University, 2012)
Forty-eight Brahman-cross male calves were fed to 26 mo of age and used to determine carcass cutability and meat quality characteristics of four muscles from intact bulls and steers castrated at 3, 7, or 12 mo of age grown under tropical pasture conditions. Longissimus lumborum (LL), Psoas major (PM), Gluteus medius (GM), and Semitendinosus (ST) steaks were aged for 2, 7, 14, or 28 d for Warner Bratzler shear force (WBSF) analysis. Live weight, carcass traits, and total subprimal yields were not affected by male sex condition. For PM, GM, and ST steaks, WBSF values were similar for steaks from intact bulls and steers castrated at all ages. For both PM and GM muscles, steaks aged for 28 d had the lowest (most tender) WBSF values and steaks aged for 2 d had the highest WBSF values. For the ST, WBSF values were highest for steaks aged 2 d. A treatment × aging interaction was detected for LL WBSF values. At 14 d of aging, LL steaks from steers castrated at 3 mo tended to have lower WBSF values than those from intact bulls. At 28 d of aging, steaks from steers had lower WBSF values than steaks from intact bulls and steaks from steers castrated at 3 mo tended to have lower WBSF values than steaks from steers castrated at 12 mo. For LL steaks from steers castrated at 3, 7 or12 mo, WBSF values linearly decreased with increased days of aging. Although all sensory panel data collected were not statistically different, LL steaks from steers castrated at 3 mo tended to have higher (more tender) scores for overall tenderness than steaks from intact bull. This study indicates that castration at 3 mo would be the recommended production practice as it provided the greatest improvement of LL tenderness over intact bulls with no differences in carcass traits or subprimal yields. The degree of improvement in tenderness due to aging is muscle dependent.
Keywords: Beef; Bulls; Steers; Aging; Tenderness; Agriculture, General (0473)